Isolation and characterization of a luminescent bacterium Vibrio SP. isolated MZ with potential application for biomonitoring of hydrocarbon biodegradation - Zahaba, Maryam (2013)
Hydrocarbon pollution is the number one pollution in global scale and including Malaysia. There are numerous reports on hydrocarbon pollution in coastal and terrestrial areas in Malaysia. Hydrocarbon wastes are generated in tonnes from petroleumNrefineries. Bioremediation of hydrocarbon pollution and wastes is being intensely pursued by local researchers. Monitoring the remediation of hydrocarbon pollution using conventional instrumental methods is time consuming. It also needs complicated sample preparation and skilled personnel and it cannot be carried out in real or near-real time. Biomonitoring has become increasingly used as a cheaper monitoring tool with near-real time results. It could also be used to monitor bioremediation progress. Luminescence bacterium assay of toxicant has been accepted by the USEPA as a biomonitoring tool for the remediation of toxicants, such as diesel and hydrocarbon sludge, with Microtox as the major tool. Microtox is based on the inhibition of luminescence of the bacterium V.fischeri by the toxicants. However, the assay must be carried out stringently at 15±1 °C,needing an incubator and precluding its use in the field. A locally isolated luminescence bacterium isolated from Selaroides leptolepis tentatively identified as Vibrio sp. isolate MZ via biochemical and molecular analysis showed a promising alternative to V. fischeri as the assay could be carried out under room temperature. Vibrio sp. isolate MZ showed optimum bioluminescence production within 25 °C to 35 °C and within pH 7.5 to pH 8.4 with 1% sodium chloride (w/v), 10 g/l peptone, 10 g/l sucrose, and 2 g/l calcium carbonate. Toxicity test for metals and sludge was done prior to toxicity test of biodegradation products of sludge. It was found that the IC50 for mercury, cadmium, and hydrocarbon sludge were 0.1 mg/l, 9.4 mg/l, and 13.26 ppm respectively. Bench scale biodegradation of 1% sludge (w/v) was set up and the degradation of sample was determined by gas chromatography with flame ionised detector (GC-FID). Based on the preliminary results obtained, Vibrio sp. isolate MZ was able to monitor the biodegradation of sludge. Therefore, Vibrio sp. isolate MZ has the potential to be used as a biomonitoring agent for hydrocarbon bioremediation.